EFEKTIVITAS PENAMBAHAN KAROTENOID KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) PADA PAKAN BUATAN TERHADAP PERFORMA IKAN KOI (Cyprinus carpio) - Haerawati Haerawati; Pither Magi Sambara (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The study aims determine an appropriate dosage of carotenoid for artificial feed in relation with the performance of Koi fish. The research used the Completely Randomized Design (CRD) with four tratments of red dragon fruit carotenoid dosage (0, 1500, 2000, and 2500 mg/kg feed) and three replications. Koi fish wasa kept for sixty days in 12 units of glass aquarium with the size of 50 cm X 40 cm X 45 cm. Each unit was equipped with a filterisation system. Feed supply was given with a dosage of 5% of the body weight per day with a frequency of two times a day at 8 a.m and 5 p.m Central Indonesia Time. The result show that the level of β-carotene in the skin of red dragon fruits was 3.452 ppm. The highest level of carotenoid in Koi fish (0.737 ppm) was found in the carotenoid dosage of 2000 mg/kg feed. Dosage 1500 mg/kged gave the colour in the colour characteristic of Koi fish. The value was 3.75 (good category in the natural assessment criteria). Furthermore, a colour gradation of Koi fish (10 red and 11 black) was found in the dosage of 2500 mg/kg feed. The dosage of 2500 mg/kg feed also showed the highest number of chromatophore cells in the pigment of Koi fish. The carotenoid of dragon fruit skin, with a dosage 2500 mg/kg feed, can be used as supplementing feed to increase characteristik and the brightness of the colour of Koi fish.